1994
DOI: 10.1111/j.1699-0463.1994.tb04865.x
|View full text |Cite
|
Sign up to set email alerts
|

An ultrastructural analysis of concordant and discordant cardiac xenografts in unmodified recipients

Abstract: Ultrastructural changes in endothelial cells in a hamster‐to‐rat and guinea pig‐to‐rat heart transplantation model are described. In the hamster‐to‐rat model, changes were minimal with an increase in cytoplasmic vesicles 4–6 h after transplantation. 16–24 h after transplantation larger vesicles appeared and the basement and cell membranes were less well defined. 42–48 h after transplantation the changes had progressed with destruction of cell membranes and the appearance of extravasated erythrocytes. At the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Unmodified recipients show a pattern classically defined as humoral but there is no consensus between the different studies, as a number of variants of the same rejection mechanism have been described (5, 19). Like Brouard et al (20), we observed severe alterations of the interstitium, with extensive edema, coagulative necrosis, haemorrhage, and with no cellular infiltration of any type.…”
Section: Discussionmentioning
confidence: 99%
“…Unmodified recipients show a pattern classically defined as humoral but there is no consensus between the different studies, as a number of variants of the same rejection mechanism have been described (5, 19). Like Brouard et al (20), we observed severe alterations of the interstitium, with extensive edema, coagulative necrosis, haemorrhage, and with no cellular infiltration of any type.…”
Section: Discussionmentioning
confidence: 99%
“…Samples of left ventricular tissue were removed immediately after sacrifice and fixed in 2.5% glutaraldehyde. The tissue was then treated after standard procedure (Nielsen et al 1994) and examined with a 208 Philips electron microscope by two of us (ABH, TH), unaware of treatment conditions. Serum analysis.…”
Section: Groupmentioning
confidence: 99%
“…Although our results exclude a cardiotoxic side effect of WF10, serial biochemical or contractile functional measurements might have shown the opposite. However, electron microscopy has been shown to be a valuable method, both to evaluate cardiac xenotransplant rejection (Nielsen et al 1994;Rose 1997;Kemp et al 2000) and druginduced cardiotoxicity (Billingham 1983). Correlational studies using ejection fraction indices and/or 31P nuclear magnetic resonance spectroscopy will be of great value in the future (Zandt et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Samples of left ventricular tissue were removed immediately after sacrifice and fixed in 2.5% glutaraldehyde. The tissue was then treated after standard procedure (Nielsen et al 1994) and examined with a 208 Philips electron microscope by two of us (ABH, TH), unaware of treatment conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation